2024
DOI: 10.1002/msc.1867
|View full text |Cite
|
Sign up to set email alerts
|

Optimising body weight in people with obesity prior to knee or hip arthroplasty: A feasibility study utilising a dietitian‐led low inflammatory diet

Furkan Genel,
Natalie Pavlovic,
Manxin Gao
et al.

Abstract: BackgroundWeight loss is recommended for people with obesity prior to undergoing total knee or hip arthroplasty. This study aimed to determine the feasibility of implementing a dietitian‐led low‐inflammatory weight‐loss diet for people with obesity awaiting arthroplasty. Secondary aims were to report weight change, patient‐reported outcomes, diet compliance, surgery deferment and diet acceptability.MethodsEligible participants were enrolled across two sequential periods; Usual Care (UC) was recruited, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…These include the absence of a control group or randomisation, as well as the short-term follow up period of 12 weeks. However, based on previous research in this patient population group [ 31 ], we are confident that minimal weight loss would have occurred amongst those not involved in the PMR weight loss program. The generalisability of the study findings is also limited by the small sample ( n = 29) of participants awaiting TKA or THA recruited from a single public arthroplasty centre.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These include the absence of a control group or randomisation, as well as the short-term follow up period of 12 weeks. However, based on previous research in this patient population group [ 31 ], we are confident that minimal weight loss would have occurred amongst those not involved in the PMR weight loss program. The generalisability of the study findings is also limited by the small sample ( n = 29) of participants awaiting TKA or THA recruited from a single public arthroplasty centre.…”
Section: Discussionmentioning
confidence: 92%
“…A recent systematic review indicated that while short-term, nonsurgical, preoperative weight loss interventions before TKA and THA produce statistically significant weight loss, it is not known whether the weight loss is clinically significant (defined as a 5% change in weight) or sufficient to improve outcomes after arthroplasty [ 30 ]. Recent attempts to manage obesity amongst participants undergoing pre-surgery optimisation have failed to achieve significant weight loss [ 31 ]. Clinical trials are clearly needed to inform both how weight loss is best achieved and how much weight loss is required to reduce the risks associated with obesity.…”
Section: Introductionmentioning
confidence: 99%